2021
DOI: 10.1186/s13048-021-00815-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of SphK1 by adipocytes mediates epithelial ovarian cancer cell proliferation

Abstract: Background Adipocytes, active facilitators of epithelial ovarian cancer (EOC) growth, have been implicated in the link between obesity and EOC. However, the current understanding of the mechanisms underlying adipocyte-induced EOC cell proliferation remains incomplete. Results We provide the first evidence showing that sphingosine kinase (SphK) 1 is critical for adipocyte-induced EOC cell proliferation. Adipocytes are capable of activating SphK1, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Obesity has been proven to be associated with a poor prognosis in ovarian cancer (93,94). Studies have demonstrated that adipocytes promote ovarian cancer progression (95,96). If metastasis was a random event in ovarian cancer, then the organs in the peritoneal cavity would be equally affected by focal metastasis.…”
Section: Adipocytesmentioning
confidence: 99%
“…Obesity has been proven to be associated with a poor prognosis in ovarian cancer (93,94). Studies have demonstrated that adipocytes promote ovarian cancer progression (95,96). If metastasis was a random event in ovarian cancer, then the organs in the peritoneal cavity would be equally affected by focal metastasis.…”
Section: Adipocytesmentioning
confidence: 99%
“…However, the exact mechanism of the adipocyte-induced c-Myc expression is not yet clear. c-Myc could be targeted by other adipocyte-regulated pathways, such as the SphK1 [ 16 , 48 ], AKT [ 25 , 49 ], and ERK [ 23 , 50 ] pathways. In addition, c-Myc could also be activated by adipocyte-secreted factors, such as estrogen [ 51 , 52 ], interleukin-6 [ 3 , 53 ], and interleukin-8 [ 3 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…SphK1, which was overexpressed in EOC tissue [ 14 ], was inversely correlated with overall survival (OS) in EOC patients [ 15 ]. Moreover, elevated SphK1 levels were associated with EOC growth [ 16 ], metastasis [ 14 ], angiogenesis [ 17 ], and chemotherapeutic resistance [ 18 ]. Furthermore, knockout of SphK1 significantly blocked the EOC progression [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that SphK1 was over-expressed in EOC tissue and was involved in EOC growth and angiogenesis [ 5 7 ]. We recently found adipocytes could activate SphK1 in EOC cells [ 6 ]. In this work, we tested the role of SphK1 in EOC metastasis induced by adipocyte-rich niche.…”
Section: To the Editormentioning
confidence: 99%
“…SphK1 catalyzes the phosphorylation of sphingosine to produce sphingosine-1-phosphate (S1P), which can act through S1P receptor (S1PR) pathway and intracellular pathway [4]. We previously showed that SphK1 was over-expressed in EOC tissue and was involved in EOC growth and angiogenesis [5][6][7]. We recently found adipocytes could activate SphK1 in EOC cells [6].…”
Section: To the Editormentioning
confidence: 99%